Fundamentals of remote sensing and airphoto interpretation - Avery, Thomas Eugene (Macmillan, 1985)
This book traces step-by-step the fundamental principles and processes involved in acquiring and interpreting aerial photographs and then in applying the data from these images to specific situations. Extensively revised to include more color plates, line drawings and photographic images this book is ideal in introducing readers to remote sensing and photographic interpretation. Overview of Remote Sensing, Photo-Optical Remote Sensing, Principles of Airphoto Interpretation, Principles of Photogammetry, Aircraft and Satellite Photography, Electro-Optical Remote Sensing, Microwave and Acoustical Remote Sensing, API Applications in Geography, API Applications in Archaeology, API Applications in Agriculture and Pedology, API Applications in Forestry, API Applications in Geology, API Applications in Engineering and Environmental Science, Computer Applications in Remote Sensing. This book is designed for anyone interested in learning more about the detection, identification and analysis of objects and features through remote sensing and photographic interpretation